Impacts of Verotoxigenic and Enterohaemorrhagic Escherichia Coli (Vtec and Ehec) on Animal, Human and Food - Widodo Suwito (Indonesian Center for Animal Research and Development, 2009)
Verotoxigenic and enterohaemorrhagic Escherichia coli, VTEC and EHEC are strains that produce a toxin on the Vero cells in vitro, therefore the toxin called verotoxin. Strain VTEC and EHEC have been isolated from human and various animal species, mainly ruminants and pigs. The prevalence of VTEC in cattle is 35%, milk 10%, cheese 1.5%. In beef meat, pork, poultry, goat and sheep is 3.7, 1.5, 1.5, 2 and 2.5%, respectively. In contrast, the human prevalence in United States, Spain and France 5 – 10, 2.5 and 3.4%, respectively. In Indonesia, nine cases of VTEC were reported by Ciptomangunkusumo Hospital and four out of nine cases were died. The verotoxin also named Shiga toxins (Stx), is active in vivo as a pathogen on the endothelial cells of the blood vessels of the gastro intestinal mucosa, kidneys, brain and other tissues of human and piglets. Verotoxin in human, ruminants and piglets causes bloody diarrhea so with ruminants. In the adult ruminants, verotoxin results in clinical signs and they act as asymptomatic carriers of VTEC and EHEC strains but in human, it produced haemorrhagic colitis (HC), haemolytic uremic syndrome (HUS) and thrombocytopenia purpura (TPP). Infection in human by the most famous EHEC strain belongs to the O157:H7 serotype, through faecal contamination or environment of either food of animal origin, or other foodstuffs (fruits and vegetables). Infection from EHEC strains could be prevented by avoiding food of animal origin and unpasteurized milk, and by taking care of food hygiene for comsumption. Key words: verotoxin, enterohaemorrhagic, VTEC, EHEC, Shiga toxin (stx), ruminant